Patient-Reported Control of Asthma, Nasal Polyposis, and Middle-Ear Symptoms in NSAID-Exacerbated Respiratory Disease - Suikkila, Anna; Hafrén, Lena; Lyly, Annina; Klockars, Tuomas; Saarinen, Riitta (Frontiers in Allergy, 2021)
Non-steroidal anti-inflammatory drug (NSAID)—exacerbated respiratory disease (NERD) is an adult-onset inflammatory condition of the upper and lower airways. It is characterized by the co-existence of asthma, nasal polyposis, and hypersensitivity to NSAIDs. Over one-fourth of patients also have symptoms of chronic middle-ear infection. The clinical course of NERD is often severe and generally requires multimodal treatment with recurrent surgical measures. Studies presenting the disease burden and subjective symptom control of NERD are limited. In this qualitative questionnaire study, we present the clinical characteristics of asthma, nasal polyposis, NSAID intolerance and possible recurrent or chronic middle-ear infection of 66 confirmed NERD patients treated at our tertiary referral center between January 2016 and May 2017. Additionally, we present the patient-reported disease control of asthma, nasal polyposis, and middle-ear symptoms on a four-category Likert scale. The proportion of NERD patients with recurrent or chronic middle-ear infection was 18%. The proportion of good or very good subjective disease control was 83% for asthma, 58% for nasal polyposis, and 33% for chronic middle-ear infection, if present. Chronic middle-ear infection is common among NERD patients and should more often be recognized as part of the entity. Together with nasal polyposis, chronic middle-ear infection seems to affect patients more than asthma. The patient's perspective of disease control should be considered when planning the interdisciplinary follow-up and treatment of NERD.